The Future Seen from the Edge of Society: Contemporary Russophone Communist Sci-Fi - Mitrofanova, Anastasia (Dějiny – teorie – kritika, 2022)
Analysing contemporary Russophone communist science fiction, this article aims to find out how this literary stream envisions the transition to the communist socio-economic formation. Communist sci-fi assumes that scientific and technological progress will inevitably be accompanied by progress in social relations and morals. The author’s position is that its closest analogy is not Soviet science fiction, but the literature of socialist realism. Contrary to the classical Marxist position that the progressive development of the human personality results from the progressive development of productive forces communist sci-fi envisions making a new person more like a miraculous transfiguration under the impact of the forces beyond human imagination and control. The author concludes that this literature implicitly states that the new people precede communist society. The research methodology consists of the critical analysis of texts produced by communist sci-fi writers that are seen in the broader context of Soviet literature of the 20th century.